Analysis of Capital Market Reactions To The Merger of Indonesian Sharia Banks: BRIS Stocks Evidence - Grisvia Agustin (Jurnal Keuangan dan Perbankan, 2022)
This study aims to obtain evidence of the stock market’s reaction to the merger of Indonesian Islamic banks and its prediction power to JCI. The variables used in this study are abnormal returns and trading volume activity with an observation period of 60 days before the event and 60 days after the event. We use 2 types of time series data, which are daily data to analyze AR and trading volume activity, and weekly data to analyze the causality relationship. The results showed that there were no differences in abnormal returns before and after the merger, but there were differences in trading volume activity before and after the merger. In addition, this study also aims to determine the reciprocal relationship using Granger causality between the JCI and BRIS stocks prices before and after the merger of Indonesian Islamic banks. The results of the study show that there is no reciprocal relationship between the Composite Stocks Price Index and the stock’s price of BRIS and vice versa.